Productive Partnerships: An effective instrument for the inclusion of vulnerable population groups in diverse contexts of Colombia - Lundy, Mark M.; Parra-Peña, Rafael Isidro; Jaramillo, Carmen Lucía; Amrein, Alexandra; Hurtado Bermudez, Jhon Jairo; González, C. (International Center for Tropical Agriculture, 2015)
In Colombia, rural development requires institutional frameworks that help to reduce the current rural-urban divide. Policy instruments that promote productivity improvements, inclusion, and collective action focused on strengthening rural competitiveness are crucial. Twelve years of experience gained from the implementation of the Rural Productive Partnerships Project (PAAP), run by the Ministry of Agriculture and Rural Development (MADR) with support from the World Bank, provides useful lessons in this regard. The importance of these lessons learned is highlighted by the results of a recent study of the Linking Farmers to Markets team of the International Center for Tropical Agriculture (CIAT), funded by the Ford Foundation. This study not only provides an overview of the positive innovative aspects of PAAP, but also proposes necessary adjustments to increase its impact.